2020
DOI: 10.7554/elife.59470
|View full text |Cite
|
Sign up to set email alerts
|

Male-predominant galanin mediates androgen-dependent aggressive chases in medaka

Abstract: Recent studies in mice demonstrate that a subset of neurons in the medial preoptic area (MPOA) that express galanin play crucial roles in regulating parental behavior in both sexes. However, little information is available on the function of galanin in social behaviors in other species. Here, we report that, in medaka, a subset of MPOA galanin neurons occurred nearly exclusively in males, resulting from testicular androgen stimulation. Galanin-deficient medaka showed a greatly reduced incidence of male–male ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…Previous studies have shown that ar expression in the brain and the pituitary regulates the expression of several hormones that can control the reproduction and social behaviours in medaka 10,43,47 . Hence, we observed the mating behaviour of a test male (homozygotes for the WT, ara KO, arb KO, or DKO alleles) with a WT female.…”
Section: Differential Effects Of the Two Ars On Mating Behavioursmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that ar expression in the brain and the pituitary regulates the expression of several hormones that can control the reproduction and social behaviours in medaka 10,43,47 . Hence, we observed the mating behaviour of a test male (homozygotes for the WT, ara KO, arb KO, or DKO alleles) with a WT female.…”
Section: Differential Effects Of the Two Ars On Mating Behavioursmentioning
confidence: 99%
“…Males perform courtship behaviours consisting of a sequence of stereotyped actions that are easily quantified 35,38,41 . Furthermore, previous studies demonstrated that Ars are expressed in the brain 42 and can control the sexually dimorphic expression of neuropeptides and biologically active nonapeptides 10,43 . Although these findings indicate that Ars are involved in a broad range of male-specific traits in medaka, the differential role of the two Ars remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed differences in the expression patterns of several neuropeptides associated with these behaviours in other systems. For example, decreased galn expression in cave-morphs versus surface-morphs could partially explain the loss of sleep or changes in appetite or aggression in cave-morphs [56][57][58] . Alterations in oxytocin cells might also be linked to changes in appetite, or the lack of social interactions (schooling) observed in cave-morphs 56,59 .…”
Section: Single-cell Transcriptomic Signatures Associated With Cave-a...mentioning
confidence: 99%
“…So far, the majority of researchers have recorded the videos of animal behavior by using video camera and manually annotated the behavioral events while replaying the videos 5 11 . However, simultaneous video-recording inevitably tends to be associated with human-errors with increasing number of cameras.…”
Section: Introductionmentioning
confidence: 99%